An obituary to Prof. GS. Nepali - Gurung, Ganesh Man (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v8i0.1130 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.227-229